2020
DOI: 10.1037/ort0000452
|View full text |Cite
|
Sign up to set email alerts
|

Homeplace: Care and resistance among public housing residents facing mixed-income redevelopment.

Abstract: Low-income communities of color experience significant political, economic, and health inequities and, not unrelatedly, are disproportionately exposed to violent crime than are residents of higher income communities. In an effort to mitigate concentrations of poverty and crime, governmental agencies have partnered with affordable housing developers to redevelop public housing "projects" into mixed-income communities and to do so within a "trauma-informed" framework. The current study analyzes how residents hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 30 publications
(35 reference statements)
0
11
0
Order By: Relevance
“…For example, within the NHPI subgroup, a large Samoan population resides in San Francisco public housing. ( Hagan et al, 2020 ) Literature has shown that both within and across ethnic subgroups there is variation in health outcomes due to differences in the sociopolitical contexts that groups occupy. ( Gee et al, 2009 , Hagan et al, 2020 ) More robust investigation is needed in samples intentionally designed to address sample size issues across racial/ethnic subgroups in order to better understand implications of findings within this AANHPI/Other group.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…For example, within the NHPI subgroup, a large Samoan population resides in San Francisco public housing. ( Hagan et al, 2020 ) Literature has shown that both within and across ethnic subgroups there is variation in health outcomes due to differences in the sociopolitical contexts that groups occupy. ( Gee et al, 2009 , Hagan et al, 2020 ) More robust investigation is needed in samples intentionally designed to address sample size issues across racial/ethnic subgroups in order to better understand implications of findings within this AANHPI/Other group.…”
Section: Discussionmentioning
confidence: 99%
“…Findings from the qualitative arm of the mixed method study from which these data were obtained provide potential insight into mechanisms driving this variation. ( Hagan et al, 2020 ) Interviews at two public housing sites emphasized that services available to residents were often not targeted to their needs in socially and geographically accessible ways. ( Hagan et al, 2020 ) Such disconnects may partially drive differences in health care utilization in public housing sites where outpatient visits are lower or emergency department visits are higher, although further research is needed to fully elucidate these nuances.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations